1999
DOI: 10.1007/bf02365743
|View full text |Cite
|
Sign up to set email alerts
|

Fracture mechanics approach to hydrogen assisted cracking: Analysis of theK-dominance condition

Abstract: We summarize the achievements of a major research line at the Department of Materials Science of the University of La Corufia (Spain) in the field of environmentally-assisted cracking in general and hydrogen degradation in particular, We analyze the meaning and significance of the fracture-mechanics approach to hydrogen-assisted cracking and study the problem of K-dominance not only over the mechanical aspects of the phenomenon but also over the environmental (physicochemical) factors affecting the entire coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5] Hudak and Wei [2] conducted crack growth rate experiments on 4340 steel in distilled water to better understand the earlier static load results of Landis and Wei, [1] which showed that K th is not unique and that stage I crack velocity is not a unique function of K when K increases with crack growth. Both were found to be dependent on the initial value of K. By testing specimens for which K remains constant during crack growth under constant load, Hudak and Wei concluded that the behavior observed by Landis and Wei is ''due, at least in part, to non-steady state crack growth.''…”
Section: MM Hall Jrmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Hudak and Wei [2] conducted crack growth rate experiments on 4340 steel in distilled water to better understand the earlier static load results of Landis and Wei, [1] which showed that K th is not unique and that stage I crack velocity is not a unique function of K when K increases with crack growth. Both were found to be dependent on the initial value of K. By testing specimens for which K remains constant during crack growth under constant load, Hudak and Wei concluded that the behavior observed by Landis and Wei is ''due, at least in part, to non-steady state crack growth.''…”
Section: MM Hall Jrmentioning
confidence: 99%
“…[2], [5], [13], and [15] given values for each of the parameters in these equations. However, use of Eq.…”
Section: B Effect Of Dd/dt (Dk/dt) On K Thmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards hydrogen diffusion, phenomenological consideration attending the stress effect on hydrogen behavior in metals yields the equation of stress-assisted diffusion under isothermal conditions as follows [5,8,16,17,25]:…”
mentioning
confidence: 99%
“…Taking into account that the diffusion driving force and flux are nil at equilibrium, it can be easily obtained [5,8,25] …”
mentioning
confidence: 99%